2021
DOI: 10.1051/shsconf/202110201008
|View full text |Cite
|
Sign up to set email alerts
|

Speak with signs: Active learning platform for Greek Sign Language, English Sign Language, and their translation

Abstract: Sign Language is used to facilitate the communication between Deaf and non-Deaf people. It uses signs-words with basic structural elements such as handshape, parts of face, body or space, and the orientation of the fingers-palm. Sign Languages vary from people to people and from country to country and evolve as spoken languages. In the current study, an application which aims at Greek Sign Language and English Sign Language learning by hard of hearing people and talking people, has been developed. The applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In recent years, many tools and applications have been developed to assist individuals in learning sign languages and translating signs into spoken language or text, significantly enhancing communication and accessibility for the deaf and hard-of-hearing community. Studies, such as those conducted in [14,15], have demonstrated the importance of sign language in enabling communication for those with hearing difficulties, and they emphasize the need for technology to facilitate access to information.…”
Section: Challenges In Sign Language Translationmentioning
confidence: 99%
“…In recent years, many tools and applications have been developed to assist individuals in learning sign languages and translating signs into spoken language or text, significantly enhancing communication and accessibility for the deaf and hard-of-hearing community. Studies, such as those conducted in [14,15], have demonstrated the importance of sign language in enabling communication for those with hearing difficulties, and they emphasize the need for technology to facilitate access to information.…”
Section: Challenges In Sign Language Translationmentioning
confidence: 99%
“…This can be achieved through various methods such as the game will meet the needs of learners . Apart from Education applications [17] , IoT has also been applied in other such as sign language learning [18] , gaming [19] and medical applications [20].…”
Section: Smart Educationmentioning
confidence: 99%
“…These studies suggest that integrated STEAM learning environments should help students investigate relevant concepts and understand how concepts support design goals. Also, STEAM could be applied to several purposes such as teaching sign language [27], foreign languages [13], [20], [24], or examination platforms [17]. STEAM through the blending of arts and technology could also help educators, regardless of their age, to implement ICT in a more fruitful way in their curiculla without feeling that they are threatened [32].…”
Section: Inventionsmentioning
confidence: 99%